Master plan Renewals Impact on Urban Fabric Transformations for Basra City - غسان جاسم محمد (Journal of Engineering and Sustainable Development, 2011)
Many literary narratives dealt with transformations in urban fabric as a product that always varies, reflecting levels of interaction between human and the surrounding environment, which is affected by time and contemporary ideologies and social, politics factors that impose requirements of change and adaptation... And due to continuation of this influence,urban fabric having transformations due to changes in the urban environment and this shift is shown evidently in the renewal of master plans for the cities, where since the early decades of the last century with the entry of motor vehicles which were considered one of the elements that having a great impact in the vocabulary of Master plans, concepts and ideas alien in the planning as reflected in its impact in the scale and proportions, and then transform the fabric details ,open space ,visual nodes and other issues respectively. So a need arises to know the impact of Master Planning Renewals on urban fabric Transformations. With these perspectives the paper problem is identified as follows: There is no clear conception to understand the impact of renewing Master Plans on transformations in urban fabric of Basra city. This paper reviewed the definition of Master plan as process of certain activities and fundamentals and also reviewing previous literature on Transformations in urban fabric and where its related to the master plan, and then studying the city of Basra fabric growth and characteristics which having different properties comparing with other traditional urban fabric for Arabic cities in terms of evolution and growth.